Англійські лексичні та термінологічні запозичення в німецькій мові - Дундій, П.Н. (Центр наукових досліджень та викладання іноземних мов НАН України, 2009)
The article deals with the process of borrowing from English language into a term system of German and considers intra- and extralinguistic factors of loanword adaptations.